Willingness to pay halal logistics among non-Muslim consumers in Universiti Utara Malaysia - Dg Ku Zunaidah, Ag Majid (2018)
Food companies in Malaysia facing serious problems to meet Halal logistics requirements because majority of Halal logistics companies in Malaysia are still reluctant to adopt Halal logistics to their business operation. The amount of logistics companies in Malaysia was 36,000 units but only 85 logistics companies implement Halal logistics. Hence, this research will help to overcome these issues by getting the information about the demand of Halal logistics. Moreover, examine whether consumers willing to pay for Halal logistics is important because logistics cost was transferred to them. Guided by Theory of Planned Behaviour (TPB), the purpose of this research is to examine the relationship of concern on Halal, perception on Halal logistics, awareness on Halal logistics and knowledge on Halal with willingness to pay Halal logistics among Non-Muslim consumers in Kedah. The survey of 300 Non Muslim students in University Utara Malaysia (UUM) was analyzed using SPSS Software to indicate the model is well accepted with reliable and valid instruments. The finding revealed that only concern on Halal and perception on Halal logistics influence consumers' willingness to pay Halal logistics. Meanwhile, awareness on Halal logistics and knowledge on Halal were found not to have a significant influence on willingness to pay Halal logistics. The result indicates that the Non-Muslim consumers' willing to pay Halal logistics because they have positive perception toward Halal logistics and they believe products that have Halal tag/label was manufactured with cleanliness and quality. The study contributed to the future investment, beneficial for manufacturers/ logistics service provider and quality of life. In addition, the findings of the study show that willingness to pay Halal logistics is differ among religion and state. However, gender does not show a significant different. This finding indicates that gender willingness to pay Halal logistics is highly dependent on one's self.